Heterotrophic nitrifying/aerobic denitrifying bacteria: Ammonium removal under different physical-chemical conditions and molecular characterization. (15th October 2019) - Carneiro Fidélis Silva, Lívia; Santiago Lima, Helena; Antônio de Oliveira Mendes, Tiago; Sartoratto, Adilson; de Paula Sousa, Maira; Suhett de Souza, Rodrigo; Oliveira de Paula, Sérgio; Maia de Oliveira, Valéria; Canêdo da Silva, Cynthia
Abstract: Biological ammonium removal via heterotrophic nitrification/aerobic denitrification (HN/AD) was characterized for two isolates from a wastewater treatment station (WWTS). They were identified as Pseudomonas balearica UFV3 and Gordonia amicalis UFV4. Their ability to remove ammonium via NH/DA was validated by chromatography, and the influence of different physical-chemical factors on removal was evaluated. The presence of genes involved in conventional nitrification and denitrification processes was investigated via PCR and comparative genomics. Both isolates removed 100% of the ammonium in a medium containing citrate as its carbon source with a C/N ratio of 8, 3% salt, pH 7 and 30 °C. Nitrogen balance showed that approximately 55% of the ammonium removed was lost as N2(g), and 45% was assimilated. Molecular characterization revealed the absence of genes involved in autotrophic nitrification in the genome of the two isolates and the presence of genes involved in anaerobic denitrification only in P. balearica UFV3, suggesting the involvement of other genes in the HN/AD process. This was the first report of G. amicalis and P. balearica with the capability for HN/AD. Highlights: This is the first report of G. amicalis and P. balearica with ability to HN/AD. Isolates can remove 100% of ammonium and convert it into N2(g) within 72 h. The ammonium removal occurs without excessive sludge production. Genes involved in NH/DA are different from those involved in conventional process.